Comparative analysis between two leading computer assisted translation tools used by student translators at Universidad Evangélica de El Salvador. - Sánchez Ruiz, Emerson Mario Ovidio
The need to communicate seamlessly and effectively has become significant and the translation market in El Salvador is highly competitive, demanding ever higher standards of performance and productivity both from experienced and novice translators. The requirements novice Salvadoran translators will have to meet are definitely going to increase as the demands for faster and accurate production of translated documents increase as well. This document contains a research study aimed towards comparing two Computer Assisted Translation Software often used by student translators enrolled in the the sixth and eighth semester of the Translation and Interpretation of the English Language Bachelor´s program at Universidad Evangélica de El Salvador.